Bahasa Inggris - Lenny Kurnia Octaviani; Anggita Putri Marshanda (Universitas Pendidikan Ganesha, 2023)
Tourism in Bali is known by its icon as the main tourist destination in Indonesia. Bali is often used as a reference model for tourism development and is a priority for tourists looking for beach and natural tourism. In addition, Bali also has the Puja Mandala, a unique religious tourist icon that becomes its own attraction. Puja mandala is a worship area consisting of five religions: Hindu, Protestant Christian, Buddhist, Catholic, and Islam. It has become a research topic for the development of Puja Mandela as a religious travel attraction in Bali. This research is carried out using qualitative methods through observations, interviews, and library studies, and the results are analyzed descriptively. The research results show that the tourist development in Puja Mandala is good, but there are still some shortcomings, such as the small number of accommodations.